Dealing with Angry Patients: Strategies for Hospital Workers - Khadijah hakami Ahmed hatan; Ghala Mohammed Tumayhi; Amal Mohammed Yahya Tumayhi; Hassan Nasser Anbari; Muhammad Nasser Ahmed Anbari; Yahya Abdullah Hassan Hzazi; Hadi Hussain Hadi Hattani; Maha Ali Alasiri; Abrar saeed aljahali; Mashael saeed hedan; Ahmed Mufareh Refdan Al shahrani; Abdurahman saleh Al Ahmari (International Journal of Medical Toxicology and Legal Medicine, 2024)
Anger is a commonly expressed emotion in healthcare settings. This prevalence is not confined to mental health care, geriatric care, or developmental disabilities, but is also seen in primary care, pediatrics, emergency rooms, and acute care inpatient areas, as well as outpatient settings. There are documented consequences of patient-held anger such as increased irritability, aggressiveness, conflictive behaviors, requests, verbal and physical assaults, and noncompliance. Anger may impact the delivery of health care and may have an effect on room turnover, length of time of the visit, and the morale of health care providers. Research in various healthcare areas indicates that an angry patient or family can escalate the visit into a crisis visit.